Economic determinants of Foreign Direct Investment (FDI) in agriculture sector based on selected developing OIC countries: an empirical study on the provincial panel data by using Stata, 2003-2012 / Intan Maizura Abdul Rashid, Nor'aznin Abu Bakar and Nor Azam Abdul Razak - Abdul Rashid, Intan Maizura; Abu Bakar, Nor'aznin; Abdul Razak, Nor Azam (Universiti Teknologi MARA, Perlis, 2017)
The purpose of the study aims to examine the economic determinants of Foreign Direct Investment (FDI) in Agriculture Sector based on selected developing OIC Countries. The agriculture sectors react as important keys in the expansion of any economy growth to eliminate the poverty issues. Therefore, the effective way to address poverty and eliminate the food deficit issues among the poorest people by enhancing the FDI in agriculture sector. Thus, besides the stimulation effect on growth, FDI can improve the quality of growth, and aid to achieving the goal of poverty reduction. In this study, the FDI in Agriculture Sector react as dependent variable and the independent variable economic determinant, list of economic growth, external debt, market size, exchange rate, size of government and natural resources in selected OIC Countries (Albania, Azerbaijan, Pakistan, Saudi Arabia, and Tajikistan).A provincial panel data from 2003 to 2012 and Pooled Ordinary Least Square (POLS), Random Effects Model and Fixed Effects Model are used to estimate the economic determinant effect of FDI in agriculture. After conduct several test such as Hausmen Test and Breusch and Pagan Lagrangian Multiplier Test, Pooled OLS Model is considered most appropriate model to apply in this study rather than Random Effects Model and Fixed Effects Model. The empirical results show that highly important in policy implementation that were related to the explanatory variables have significant effect on FDI in agriculture sector. Based on the empirical results, the government should be focused and paid attention all the determinants, particularly for external debt, market size and natural resources. These three determinants were the most significant with the foreign direct investment in Agriculture sector in OIC countries. However, the other three variables, economic growth, exchange rate and size of government will have the negative effect on FDI.